Statistical reasoning and methods - Johnson, Richard Arnold. (Wiley, 1998)
About statistics. Organizing data and describing patterns. Describing bivariate data. Probability-the basis for inference. Random variables and probability distributions. Normal distribuitons. Variation in repeated samples-sampling distributions...